Influence of “Gema Cermat” Education to Increased Hb Levels for Pregnant Women in Kediri – East Java - Hanie Kusuma Wardani; Hanni Prihastuti Puspitasari; Yuni Priyandani (Universitas STRADA Indonesia, 2023)
The prevalence of iron deficiency anemia in pregnant women globally reaches 52% in developing countries, including Indonesia. The impact of anemia on pregnant women is premature birth, LBW, bleeding, and even the mother and baby's death. To overcome this, the Indonesian government has ironic-folic acid (IFA) supplementation program for pregnant women with at least 90 tablets during their pregnancy. This program has walked since the 1990s, but anemia in Indonesia is still high (48.9%). Because of these issues, the Ministry of Health gave education for increased use of IFA in pregnant women, namely